Positional changes in the mandibular proximal segment after intraoral vertical ramus osteotomy: Surgery-first approach versus conventional approach - Jung, Seoyeon (Korean J Orthod, 2020)
OBJECTIVE: To compare postoperative positional changes in the mandibular proximal segment between the conventional orthognathic surgery (CS) and the surgery-first approach (SF) using intraoral vertical ramus osteotomy (IVRO) in patients with Class III malocclusion. METHODS: Thirty-eight patients with skeletal Class III malocclusion who underwent bimaxillary surgery were divided into two groups according to the use of preoperative orthodontic treatment CS group (n = 18) and SF group (n = 20). Skeletal changes in both groups were measured using computed tomography before (T0), 2 days after (T1), and 1 year after (T2) the surgery. Three-dimensional (3D) angular changes in the mandibular proximal segment, condylar position, and maxillomandibular landmarks were assessed. RESULTS: The mean amounts of mandibular setback and maxillary posterior impaction were similar in both groups. At T2, the posterior portion of the mandible moved upward in both groups. In the SF group, the anterior portion of the mandible moved upward by a mean distance of 0.9 ± 1.0 mm, which was statistically significant (p < 0.001). There were significant between-group differences in occlusal changes (p < 0.001) as well as in overjet and overbite. However, there were no significant between-group differences in proximal segment variables. CONCLUSIONS: Despite postoperative occlusal changes, positional changes in the mandibular proximal segment and the position of the condyles were similar between CS and SF, which suggested that SF using IVRO achieved satisfactory postoperative stability. If active physiotherapy is conducted, the proximal segment can be adapted in the physiological position regardless of the occlusal changes.